REMOTE EXPERMENTATIONS OF ARTIFICIAL INTELLIGENCE IN EDUCATION (International Journal of Food and Nutritional Sciences, 2022)
Research on the application of visual artificialintelligence (AI) in education has advancedsignificantly in recent years. should take advantageof the opportunity to gather a lot of data in manysettings and circumstances